Analysis of heterogeneity in nonspecific PEGylation reactions of biomolecules. Issue 7 (24th April 2013) - Hakem, Ilhem F.; Leech, Anna M.; Bohn, Justin; Walker, Jeremy P.; Bockstaller, Michael R.
<x xml:space="preserve">Abstract</x> The compositional heterogeneity associated with polymer conjugation reactions of biomolecules is analyzed for the particular case of nonspecific PEGylation reactions. It is shown that the distribution of the number of PEG moieties grafted to biomolecules such as proteins is a binomial‐type function of two parameters—the reaction efficiency as well as the number of binding sites per biomolecule. The nature of this distribution implies that uniform compositions are favored for increasing number of coupling sites per biomolecule as well as for increasing efficiency of the modification process. Therefore, the binomial distribution provides a rationale for the pronounced heterogeneity that is observed for PEGylated small enzyme systems even at high coupling efficiencies. For the particular case of PEGylated trypsin it is shown that the heterogeneity results in a broad distribution of deactivation times that is captured by a stretched exponential decay model. The presented analysis is expected to apply to general modification processes of compounds in which partial functionalization of a fixed number of reactive sites is achieved by means of a nonspecific coupling reaction. © 2012 Wiley Periodicals, Inc. Biopolymers 99: 427–435, 2013.